Evaluation of Tenderplus.id Application User Experience using USE Questionnaire - Anggraini, Nadia Rahmi Nur; Wahyuni, Elyza Gustri (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
E-procurement is a process of procuring goods and services that utilizes information and communication technology. Service providers usually access the Electronic Procurement Service (LPSE) website to carry out the e-procurement process. The LPSE website displays hundreds to thousands of government and non-government tenders, which can often reduce the effectiveness of the tender process due to the amount of information that must be managed. To address this issue, the Tenderplus.id application was developed, which is designed to monitor the latest tender packages in the Indonesian government's LPSE. The app features real-time notifications sent via WhatsApp and Email to service providers according to their company preferences and qualifications. The Tenderplus.id application user experience was measured using the USE Questionnaire (Usefulness, Satisfaction, and Ease of Use Questionnaire) method, which evaluates four main variables: usefulness, ease of use, ease of learning, and satisfaction, using a Likert Scale from one to five. The evaluation results show that the overall user experience obtained a percentage value of 83.6%, which is categorized as very feasible. The percentage details for each variable are usefulness of 87.8%, ease of use of 83.3%, ease of learning of 77.5%, and satisfaction of 84%. Implementation and testing of this application showed very positive results, strengthening the conclusion that Tenderplus.id is an effective solution to the problems faced in managing electronic tenders.